(untitled) (Journal of the College of Basic Education, 2022)
The design of the advertisement in its overall structure is a system of interrelated elements, each of which works to achieve the attraction of the recipient. Consequently, we find a visual structure represented by the final structural form of the design, which the visual effects propose to us after taking shape, size and color to become visual stimuli. And their effective use, improving the design aspect of the ads in question Based on the visual effects achieved by the composition of the overall structure of the text and the direct impact it has on the recipient, the problem of research is illustrated by the following question: What are the determinants of visual effects in the structure of advertising design? What is their impact on understanding the design idea? The objective of the research is determined in: - Detection of visual effects and their role in the structure of the design of the advertisement, the research is determined objectively in the study of visual effects in the structure of advertising design and place in the commercial ads of Coca-Cola in the United States and in 2017, The research in the second chapter deals with the topics of the forces of visual influence and achievement of the idea and attraction and gravity and the process of visual reception and visual effects and relations resulting in the design of advertising and components of the structure of the design of the visual elements and design foundations affecting the construction of advertising design, In the third chapter, the researcher came up with a set of findings, conclusions, recommendations and only one proposal